Chemical characterization of arabic gum- chitosan-propolis beads and determination of α-amylase inhibition effect: Arabic gum- Chitosan-Propolis Beads and Their Inhibition Effect on α-Amylase - Keskin, Merve (Progress in Nutrition, 2020)
Propolis is a resinous mixture collected by honey bees from various plant secretions, tree bark andleaves. It has been used as a natural and supplementary food, increasing the body’s defense mechanism against infections. It has many biological activity such as antioxidant, antimicrobial, antitumor, anti-inflammatory and antidiabetic effect etc. Because of its resinous structure, propolis should be used as extracts and ethanol/water solution (70%) is the best solvent for extraction of raw propolis. The ethanol solution limits the consumption of this valuable natural product in foods and apitherapy. Propolis extract was microencapsulated using Arabic gum and chitosan to reduce the limiting effect of ethanol. Inhibition effect of microcapsules on α-amylase enzyme was investigated. The encapsulation efficiency was found 73.46% and the Arabic gumchitosan-propolis capsules (beads) size was found 784.1 nm in average. Antioxidant capacity of propolis extract was found 347.16 µg Trolox/g. Release properties of capsules were determined and capsules were released in the pH 7.4 and pH 1.5. Inhibition effect on α-amylase enzyme was found (IC50) 0.55 mg/mL. Itis clear that Arabic gum-chitosan-propolis capsules could be used as a supplementary food in the treatmentof Diabetes Mellitus.